A Review of Sharia Economic Law on the Fish Price Determination Mechanism Between Fishermen and Suppliers - Untung, Ahmad; Umasugi, Nirwan; Marasabessy, Zainal Abidin; Wajo, Abd. Rauf; Jasmin, Jasmin; Ahmad, Samlan; Harwis, Harwis (Global Education Journal, 2025)
A Review of Sharia Economic Law on the Fish Pricing Mechanism between Fishermen and Suppliers at the Independent Tuna Fishermen's Cooperative in Jikotamo Village. This study aims to analyze the fish pricing mechanism between fishermen and suppliers in Jikotamo Village and review these practices from the perspective of Sharia economic law. The research method uses a qualitative approach with a focus on the Independent Tuna Fishermen's Cooperative in Jikotamo Village, South Halmahera Regency. Data were collected through in-depth interviews and field observations, then analyzed using Sharia economic principles related to justice, transparency, and the prohibition of riba and gharar practices. The results show that the market structure is uncompetitive with dominant suppliers determining prices unilaterally. This imbalance results in a disproportionate distribution of added value, with fishermen receiving a relatively small share of the total added value. From the perspective of Sharia economic law, the fisheries supply chain has met the requirements for transaction validity (sahih) in muamalah fiqh, but needs improvement in information transparency, fair distribution of profits, and resource efficiency. The study recommends implementing a transparent pricing information system, strengthening the capacity of fishing cooperatives, subsidizing production inputs, and establishing direct partnerships with companies.